An Analysis on the Use of Derivational and Inflectional Morphemes in English Song Lyrics on Maher Zain’s “Forgive Me” Album - Yuli Purwanti (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
The primary thing to be learned in mastery a language is word. Word is dealing with morphology, because morphology influences spelling, reading comprehension, and vocabulary. In the way of understanding the meaning of vocabulary, language users need to learned morphology, especially derivational and inflectional morphemes. This study was designed to identify the derivational and inflectional morphemes and the functions of each derivational and inflectional morphemes are used on Maher Zain’s “forgive me” album. The result of this study are; (1) There were 13 derivational morphemes and 76 inflectional morphemes, and (2) The functions of every morphemes used on Maher Zain’s “forgive me” album, consist of function as adjective, plural, verb, noun, and adverb.